Comparative Study of Propofol Versus Thiopental Sodium with Succinylcholine for Laryngeal Mask Airway (LMA) Insertion - Karmakar, Chandra Shekhar; Rahman, Md Afzalur; Karim, Mohammad Rezaul; Islam, Monirul; Islam, Md Shahidul; Rahman, Md Lutfur; Alam, ABM Muksudul (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: The increasing emphasis on day case anaesthesia has lead to the greater use of the laryngeal mask airway (LMA) as an alternative to intubation. Laryngoscopy and tracheal intubation are noxious stimuli, which cause a reflex increase in both sympathetic and sympathoadrenal activity that may result in tachycardia, hypertension and dysarrhythmias. Insertion of Laryngeal mask airway (LMA) is associated with less haemodynamic changes, minimal increase in intraocular and intracranial pressure and lower incidence of sore throat. Still its insertion requires sufficient depth of anesthesia to prevent airway reflex (gagging, coughing nd spasms). To insert LMA successfully propofol is the most frequently administered medication. But most of all recommend not using propofol singly for LMA insertion. Thiopental can’t suppress the upper airway reflexes as propofol but with low dose succinylcholine upper airway reflexes are attenuated so combination of thiopental sodium with succinylcholine may be another choice of drug. Objectives: This Prospective study was conducted to evaluate the effectiveness of Thiopental sodium and Succinylcholine for insertion of the LMA in comparison with Propofol. Methods: This interventional study was carried out in Sixty patients, aged 3-45 years who were scheduled for elective surgical procedure under general anaesthesia in ShSMCH. Patients were randomly assigned to two groups by odd and even number basis. In Group-1 (N1=30), LMA was inserted after induction with Thiopental sodium (5 mg/kg body weight i.v.) and Succinylcholine (0.5mg/kg i.v); in Group-2 (N2 = 30), the LMA was inserted with Propofol (2.5mg/kg i.v). Jaw relaxation, incidence of coughing- gagging , overall insertion condition and haemodynamic changes were observed. Results: Grade of jaw relaxation in Group-1 was Good in 93.3%, incomplete in 6.7% and 0% poor but in Group-2, 86.7% was good 10% incomplete and 3.3% was poor. Coughing occurred in 33.3% of patients in the Group-2 and there was only 10% in succinyl group (P=0.028) which is significantly higher in Group-2. Overall insertion condition in Group -1 was excellent in 86.7%, Good in 10% cases and poor in only 3.3% cases on the other hand in Group-2 excellent in 53.3%, Good in 33.3% cases and poor in only 13.3% cases (P=0.019). Conclusion: There was statistically significant difference in jaw relaxation in two groups and incidence of Gagging or Coughing is higher in Group-2. Overall insertion condition was significantly better in Group-1. We concluded that Thiopental sodium with low dose Suxamethonium is an effective alternative of Propofol. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 11-15